Ambivalencias y límites de la literatura como objeto para el estructuralismo - Tuset Mayoral, Vicenç (Centro de Estudios de Teoría y Crítica Literaria, IdIHCS - CONICET. Facultad de Humanidades y Ciencias de la Educación. UNLP, 2014)
We shall delineate a sort of trajectory of the structuralist paradigm within literary criticism through the different changes its object –literature– has gone through. Structuralism based its productivity on the irreducible dichotomies it proposed, such as langue / parole. However, literature resisted the reduction of its multiplicity to such categories. Thorough structuralist analyses dealing with such resistances will not only help to visualize the limits of the method, it will also contribute to establish a whole new set of problems for contemporary literary criticism.